Causes of drug resistance and glioblastoma relapses - A. A. Mitrofanov; D. R. Naskhletashvili; V. A. Aleshin; D. M. Belov; A. Kh. Bekyashev; V. B. Karakhan; N. V. Sevyan; E. V. Prozorenko; K. E. Roshchina (Опухоли головы и шеи, 2021)
Glioblastoma multiform^ is one of the most aggressive malignancies, wich standard of treatment not changed over the past decade, and the average life expectancy from diagnosis to death does not exceed two years in the most optimistic trials. The review examines the features of the glioblastoma microenvironment, its genetic heterogeneity, the development of recurrent glioblastoma, the formation of drug resistance, the influence of the blood-brain barrier and the brain lymphatic system on the development of immunotherapy and targeted therapy. Molecular subgroups of glioblastomas with an assumed prognostic value were analyzed. It was determined that numerous relationships between glioblastoma cells and the microenvironment are aimed at ensuring tumor progression, and also cause a state of reduced effector function of T cells. Data on the development of future molecular-targeted therapies for four types of cancer cells based on their different properties and response to therapy are summarized: primary GSC, RISC cells, and proliferating and postmitotic non-GSC fractions. The penetration of blood-brain barrier with chemotherapeutic drugs and antibodies currently remains the main limitation in the treatment of glioblastoma. The resulting analysis of the causes is reduced to the following conclusions. A detailed understanding of the evolutionary dynamics of tumor progression can provide insight into the related molecular and genetic mechanisms underlying glioblastoma recurrence. The most promising methods of treatment for glioblastoma are combined therapy using immune checkpoint inhibitors in combination with new treatment methods -vaccine therapy, CAR-T-cell therapy and viral therapy. A deeper study of the mechanisms of drug resistance and acquisition resistance, biology and subcloning clonal populations of glioblastoma and its microenvironment, with active consideration of combined trips to the treatment will increase the survival rate of patients, and may lead to stable remission of the disease.